Doing Business in the 21st Century with the New Generation of Chinese Managers: A Study of Generational Shifts in Work Values in China - Ralston, David A.; Egri, Carolyn P.; Stewart, Sally; Terpstra, Robert H.; Kaicheng, Yu (Journal of International Business Studies, 1999)
Our goal is to develop a profile of Chinese managers, and in particular a profile of the New Generation of Chinese managers. The purpose for developing this profile is primarily to provide relevant information for non-Chinese business people, especially Westerners, who plan to engage in business in China. This profile is based on measures of individual values (Individualism, Collectivism and Confucianism) relevant to China and business. Our findings suggest that the New Generation manager is more individualistic and more likely to act independently, while taking risks in the pursuit of profits. However, these New managers are, likewise, not forsaking their Confucian values. Thus, they may be viewed as crossverging their Eastern and Western influences, while on the road of modernization.